Ten years of application of sewage sludge on tropical soil. A balance sheet on agricultural crops and environmental quality - Melo, Wanderley [UNESP]; Delarica, Denise [UNESP]; Guedes, Ana [UNESP]; Lavezzo, Letícia [UNESP]; Donha, Riviane [UNESP]; de Araújo, Ademir; de Melo, Gabriel; Macedo, Fernando [UNESP] (Elsevier, 2018)
Sewage sludge (SS) has been used in agriculture on a large scale in Europe. In tropical climate conditions, due to rapid organic matter degradation, SS can provide toxic elements that can cause damage to the environment. We evaluated an area that received doses of SS for 10 years compared to mineral fertilization. The biogeochemical parameters (amylase, cellulase, invertase and dehydrogenase activity, carbon microbial biomass, basal respiration, metabolic quotient, soluble carbohydrates, total carbohydrates and glucose) and maize agronomic performance were evaluated. There was no increase of organic matter in the area due to the SS application. However, the application of SS for 10 consecutive years influenced the biogeochemical parameters evaluated in a similar way to the area that received mineral fertilizer. The SS proved efficient in completely replacing P fertilization and micronutrients. SS can also partially replace N fertilization without reducing maize productivity.
Keywords: Biosolids; Soil biological activity; Soil enzyme; Soil quality; Trace elements